Transformation of a Business Model Triggered by a Scandal with Internal Branding as a Lever: - Kayoko Honjo; Kei Kuriki (Maketingu Janaru, 2022)
How does a company restore trust and performance when it has been scandalized? Axas Corporation, a temporary staffing company for IT engineers, received an administrative action from the Department of Labor in 2018. As of 2022, knowledge of the company’s philosophy and vision has become more widespread, and its business performance continues to grow. In this paper, we follow Axas’s efforts chronologically and find Kotter’s (1995, 2012) 8-step process of corporate transformation. In particular, we confirmed that the unintended scandal itself further accelerated the internal branding process. We conclude that (1) internal branding is an effective tool for transforming organizational culture, and that Axas (2) showed short-term results, (3) reversed the crisis to increase its centripetal force, and (4) promoted interpretation of its philosophy and vision at the frontline, which (5) provided new growth opportunities through a change in the business model.